2012
DOI: 10.1088/0953-8984/24/21/215404
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and anelastic anomalies associated with the antiferromagnetic ordering transition in wüstite, FexO

Abstract: The elastic and anelastic properties of three different samples of Fe(x)O have been determined in the frequency range 0.1-2 MHz by resonant ultrasound spectroscopy and in the range 0.1-50 Hz by dynamic mechanical analysis in order to characterize ferroelastic aspects of the magnetic ordering transition at T(N) ~ 195 K. No evidence was found of separate structural and magnetic transitions but softening of the shear modulus was consistent with the involvement of bilinear coupling, λe(4)q, between a symmetry-brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 122 publications
1
13
0
1
Order By: Relevance
“…The argument that twinning leads to smooth martensitic transformations (which untwinned material cannot do) was also proposed by Ball and James [120], who carefully characterized their symmetry conditions to provide optimal adaptation of the domain structures to the imposed boundary condition of the invariant plane. Similarly, Zhang et al [121] investigated magnetic systems and showed that smooth transformation behavior in wüstite could only be possible if the strain relaxation was optimized.…”
Section: Tweed Structure and Strain/orientational Glass-like Systemsmentioning
confidence: 99%
“…The argument that twinning leads to smooth martensitic transformations (which untwinned material cannot do) was also proposed by Ball and James [120], who carefully characterized their symmetry conditions to provide optimal adaptation of the domain structures to the imposed boundary condition of the invariant plane. Similarly, Zhang et al [121] investigated magnetic systems and showed that smooth transformation behavior in wüstite could only be possible if the strain relaxation was optimized.…”
Section: Tweed Structure and Strain/orientational Glass-like Systemsmentioning
confidence: 99%
“…Other systems in which linear-quadratic coupling is important are Fe x O, MnO, (La, Pr)AlO 3 and selected pnictides [99][100][101][102][103][104][105][106]. The topology of order parameter variations in NdCo 2 is expected to be closely similar to that of Fe x O, though the relevant instability in the latter may be due to a soft acoustic mode [99], rather than a cooperative Jahn-Teller distortion.…”
Section: Linear-quadratic Coupling Between Jahn-teller and Magnetic Omentioning
confidence: 99%
“…7 se observa que por debajo del máximo la curva FC conserva una tendencia aproximadamente constante de la susceptibilidad magnética, lo que sugiere la ocurrencia de un comportamiento de tipo ferrimagnético [36]. El máximo valor observado en todas las muestras (M10-M40): cerca de T ≈ 120 K, se atribuye a la transición de Verwey de la magnetita [37].…”
Section: Resultados Y Discusiónunclassified